Phytochemical Screening, GC-MS Analysis of the Methanolic Extract of Bracken Fern (Pteridium aquilinum) - Aliyu Ahmed, IBRAHIM; Mohammed Jimoh, ADISA; Usman Ibrahim, HAMZA; Khadijat, ABDULSALAM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Bracken, a type of large fern belonging to the genus Pteridium aqulinum and family Dennstaedtiaceae, is found in various regions of the world and has been classified as carcinogenic to humans. It is also known for its anti-parasitic and anti-ascaris properties because of its ability to kill small intestinal ascaris roundworms in the body. This plant synthesize non nutritive phytochemicals with potential toxicity and health benefit. For instance, anti-nutrients, which are natural or synthetic compounds that interfere with the absorption of nutrients by binding to vitamins and minerals, preventing their uptake, or inhibiting enzymes. Literature on the phytochemical screening of bracken is limited; Thus, this research was carried out to access the anti-nutrient, phytochemical constituents and GC-profiling of methanol extract of bracken fern was carried out. Fresh plant samples were collected from Cece, in Lapai Local Government, of Niger State and samples were identified by certified botanist. The results of the study shows that the percentage yield of the methanolic extract of stem was higher than that of the leave. It also shows the presence of terpenoids in both extracts but absence of tanins. Stem is rich in flavonoid and alkaloid while leave is rich in saponin and phenolic compound. Both leaves and stem contains higher content of anti nutrients in the range (mg/kg) cyanide (5.197 - 3.063), oxalate (2.112 - 2.843) and phytate (0.951 - 0.798). GC-MS analysis reveals that presence of bioactive components. The major constituents were 1,3 butadiene (19.60 %) for leave, spiro[4.5]decan-2-one at 33.90 and 12.08 % for leave and stem extract respectively. Anthracene and its derivatives were present in major amount in the leave and stem extract. These are physiologically important bioactive molecules with anti-inflammatory, antibiotic, anticancer and antimalarial properties that can be isolated for treatment. In addition to other industrial applications such as used as an antioxidant in polymers, production of rubber and lubricants.